Strategi Manajerial Kepala Sekolah dalam Meningkatkan Literasi Digital Guru - Noor Wachidatur Rochmah, Shofia; Hidayati, Dian; Rizqon Mubarok, Arian (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2023)
Digital literacy needs to be done by an educator, because it will make it easier to obtain, understand and disseminate information on the learning process. Therefore, this study aims to find out and explain the managerial strategies carried out by school principals in increasing teacher digital literacy. This study uses a qualitative approach with collection techniques through interviews and documentation. The participants in this study were the principal and teachers of SMP Negeri 4 Sekayam. The data that has been collected is then reduced, data is presented, and conclusions are drawn. This study concludes that the managerial strategy of the principal of SMP Negeri 4 Sekayam in increasing teacher digital literacy is: 1) Doing planning by analyzing needs (looking at the state of teachers in digital use, availability of tools, and also the access needed); 2) Providing the facilities needed to increase digital literacy, such as providing tablets, Chromebooks, and providing internet access in the form of Wifi; 3) Involve teachers in organized training, such as training conducted through digital forums such as Zoom Meetings; 4) Evaluate and make improvements in the future.